The Application Of Theory Health Belief Model To Prevention Of Scabies In Santri Of The Islamic Boarding School Al – Ishlah Kediri - Elok Kusuma Wardhani, Febe; Wardani, Ratna; Maulina Nurikasari (Journal of Global Research in Public Health, 2019)
Health belief model is a model that is used to describe an individual's belief in healthy behavior, so that individuals will conduct healthy behavior, such healthy behavior can be in the form of prevention and use of health facilities. The purpose of this study was to determine the relationship between Health Belief Model and prevention of scabies, namely personal hygiene and environmental sanitation.The research design used was cross sectional with a population of 185 female students at the Al - Ishlah Islamic Boarding School in Kediri Regency. Respondents were taken using simple random sampling technique which was 126 respondents. The instrument in this study was conducted using a questionnaire with ordinal regression test between personal hygiene and Health Belief Model.The results of personal hygiene research, it is known that good categories are 30 (14%), enough categories are 71 (51%), and less categories are 25 (35%). While the results of the Health Belief Model research revealed that the good category was 36 (40%), enough categories were 59 (52%), less categories were 31 (8%). From the results of data analysis between Personal Hygiene and Health Belief Model Theory obtained p value = 0.927> α = 0.05, so that H0 was accepted and H1 was rejected thus there was no relationship between the Health Belief Model Theory with personal hygiene and environmental sanitation.Thus, no matter how good a person's personal hygiene and environmental sanitation around him, it does not determine the Health Belief Model or the perception of an individual. Copyright © 2018 STIKes Surya Mitra Husada. All rights reserved.